L'applicazione di un'analisi multivariata allo studio dell'attività bottinatrice dei bombi in un ambiente dell'Appennino centrale (Hymenoptera Apoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
This article shows the results of the observations carried out over a year, in three various habitat of a valley of Central Apennines, inside the National Park of Abruzzi, Lazio and Molise, concerning Bombus and Psithyrus species present and their foraging activity. Applaying the Principal Components Analysis (PCA) to data recorded it was possible to value, on the hand, the activity of the various species of bumblebees and, on the other, the role played by the botanical species visited towards these pollinating insects. Finally, the relationship between the Bombus and Psithyrus species more interesting and the plants more important for their forage in a mountain habitat are commented on; the knowledge of these factors certainly provides with information about habitat quality and the synergies that cooperate on the protection of the environment.
Keywords: Bombus; Foraging activity; Central Apennines; Principal Components Analysis